The Performance of Sulfamic, Acetic, and Citric Acid as An Alternative Carbonate Scale Dissolution at Laboratory Scale - Meyliana Wulandari; Verawati Verawati; Isalmi Aziz; Nofrizal Nofrizal; Rachmi Kartini; Pandian Bothi Raja (Scientific Contributions Oil and Gas, 2025)
Calcium carbonate scale is being considered one of the challenges being faced by the oil and gas industry, as it is disrupting production activities. Acidification using hydrochloric acid is being widely applied as a scale remover; however, this reagent is being recognized as highly corrosive. Hence, this study is aiming to investigate the effect of combining sulfamic acid, citric acid, and acetic acid in ratios of 9:3:3, 6:6:3, and 3:9:3 at temperatures of 35°, 45°, and 50 °C on an environmentally friendly scale dissolution.The percentage of scale dissolution from the three acids is being compared with 5, 10, and 15% hydrochloric acid at temperatures of 35°, 45°, and 50°C using the gravimetric method. The results of the study on a laboratory scale are showing that the largest percentage scale solubility is being obtained with a ratio of sulfamic acid: citric acid: acetic acid of 9:3:3 of 65.79% at a temperature of 50°C. When compared with 5% HCl at 50°C as a control, scale dissolution is reaching 63.49%.This result is being supported by scanning electron microscope data, which are showing that the surface of the scale on the pipe after treatment with three acid combinations is having a smoother surface morphology compared to using commercial scale removal (HCl). The use of three acid combinations in this study is serving as an alternative to commercial-scale removal.